Understanding and Implementing Islamic Law: Challenges and Solutions in Modern Contexts - Alia, Nur; Subli, Mohamad; Apriyanti; Nazhar (Antmind Review: Journal of Sharia and Legal Ethics, 2024)
Sharia law is an important element in Islamic law that includes rules and principles that govern various aspects of Muslim life, including worship, muamalah, and social ethics. This article analyzes the basic concept of sharia law which is divided into taklifi and wadh'i laws, as well as how relevant they are in answering challenges in the modern era. In Indonesia, the implementation of sharia law is faced with internal challenges such as stagnation of ijtihad, diversity of interpretations, and lack of trust in sharia legal institutions. External challenges include friction with the secular legal system, globalization, and human rights issues. To overcome this problem, it is necessary to update thinking through contextual ijtihad, strengthening education and literacy of sharia law, reforming legal institutions, and harmonizing sharia law with the national legal system. With a progressive and inclusive approach, sharia law can continue to be relevant in creating a just and prosperous society, as well as making a significant contribution to shaping global ethics that support social justice and sustainable development. This article offers an applicative solution to ensure that sharia law remains a relevant moral guideline in the midst of dynamic social change.